Manuela Romano. 2024. Metaphor in Socio-Political contexts. Berlin and Boston: De Grouter Mouton. 340 pp. ISBN 9783111001258 - García Romero, Margarita (Complutense Journal of English Studies, 2025)
Academic review of the volume entitled Metaphor in Socio-Political Contexts, edited by Manuela Romano and published in 2024 by De Grouter Mouton.